Visible and invisible symbols of organizational culture in Plitvice Lakes National Park in Croatia - Mihanović, Damir (Advances in business related scientific research journal, 2025)
Human society created culture and it is the result of human physical and mental work. Every business organization or company is in a system that surrounds it, regardless of the amount of their income, invested capital or number of employees. Organizational culture as a scientific discipline represents the way of life and work of a company and is defined as the atmosphere in the organization. Organizational culture is an important factor in the business and development of a company. It is important because it defines most of what is done and how it is done, which leads to a reduction in ambiguity and guides employees on how they should perform their work. Using interviews as a research method, we investigated and analyzed visible and invisible symbols of organizational culture in the example of our oldest and largest national park in the Republic of Croatia - Plitvice Lakes National Park
Keywords: business success; organizational culture; visible and invisible symbols